Linking Social Protection and Humanitarian Assistance in the Philippines - Aldaba, Fernando (World Bank, Washington, DC, 2019)
There is an increasing amount of literature discussing the integration of humanitarian assistance into social protection systems or the linkage of disaster risk responses with specific social safety net programmes. The nexus maybe seen through synergies via common frameworks, platforms and systems utilized. The Philippines continues to tackle the problems of poverty and vulnerability among its 100 million population. It lies in the “Pacific Ring of Fire” and is visited regularly by typhoons, ravaged by flooding, and occasionally hit by destructive earthquakes. It also has two long running conflicts with rebel groups that have displaced thousands of its citizens in hot areas. Despite being a middle income country and owing to the recurrent nature of crises, the country has a permanent presence of humanitarian actors (UN agencies, international, and national NGOs) ready to complement government efforts during emergencies. This specific case study showcases the linking of humanitarian assistance and social protection in two instances where cash transfer for relief and recovery by humanitarian agencies, the World Food Programme (WFP) and United Nations Children’s Fund (UNICEF), successfully “piggybacked” on the Pantawid Pamilya Pilipino Program (4Ps), a lead social protection programme of the Department of Social Welfare and Development (DSWD), during the aftermath of typhoon Haiyan (2013).